Comparative Evaluation of Generalized Multicell Impedance Source Inverter for Drives - V. Raghavendra Rajan; C.S. Ajin Sekhar; R. Hemantha Kumar; M. Sasikumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Voltage-Source Inverter is limited by its only voltage step-down operation. In adding with extra boosting the flexibility is kept active for  the number of  semiconductors which is unchanged, voltage-type Z-source inverter was earlier proposed. These new classes of inverter is generally less sensitive to electromagnetic noises. However, their boosting capabilities are anyhow less with high component stresses and poorer spectral performances caused by low modulation index ratios. Their boosting gains are, therefore, restricted in practice. To overcome these we use the generalized switched-inductor Z-source inverter is proposed, By comparing with PWM technique and SPWM technique, whose extra boosting abilities and other advantages have been verified in simulation analysis and experiment.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5128